Strategi Belajar Mahasiswa terhadap Pengembangan Keterampilan Berbicara - Citra Kusumaningsih; Baharuddin JH; Finny Anita (IKIP PGRI Pontianak, 2020)
In the current pandemic situation, reaching the goals of learners’ speaking skill fluently and accurately are not enough only determined by the lecturers’ strategy but also learners’ enthusiasm to use appropriate speaking learning strategy. The presents study aimed to identify what speaking learning strategy used by the learners, different strategies used by learners’ who are having low and high achievement, and then the dominant strategy employed by the learners. The study applied descriptive study, then the participants were 50 third semester students, chosen from 5 classes of English education study program of IKIP PGRI Pontianak. The tools of collecting data, the participants were asked to fill a questionnaire and to do a speaking test. The findings revealed all strategies almost used by the learners to develop their speaking skill, meanwhile the different strategies used by the students who are having low and high achievement are found in frequency of use the strategies and varieties of strategy in learning speaking skill. From the six strategies of learning speaking skill, as indicated in this study, the dominant strategy which have been employed by the learners is afektif strategy.